Irony as Expression (of a Sense of the Absurd) - Mitchell Green (Baltic International Yearbook of Cognition, Logic and Communication, 2018)
Situational irony is, first, explained as a severe violation of one or more established, non-moral norms; such violation constitutes that situation’s absurdity. The classical “inversion” theory of communicative irony associated with Cicero and Quintilian, as well as its refinement in terms of the notion of conversational implicature (Grice 1989), are then shown to be inadequate.The echoic (Sperber (1984), Wilson (2006), Wilson & Sperber (2012)) and pretence (Currie 2010) theories are also shown to fail to account for the broad range of communicative irony, although they each contain valuable insights. Further, both theories hold that ironic speakers express attitudes but do not explain how they do so. On the basis of prior work by Green conceptualizing the notion of expression as signaling and showing a psychological state, we defend a view of communicative irony as expressing a sense of a situation’s absurdity. The view generalizes beyond absurdity to encompass expression of a sense of situations’ silliness, wackiness, or goofiness, and accommodates milder forms of irony such as we find in meiosis.
Keywords: Irony